Pengaruh Good Corporate Governance (GCG) Terhadap Financial Distress Saat Pandemi Covid-19: Studi Empiris pada Perusahaan Badan Usaha Milik Negara yang Terdaftar pada Bursa Efek Indonesia pada Tahun 2019-2023 - Fathur Rahman As Shiddiq; Fitra Dharma; Agrianti Komalasari; Ayu Dwiny Octary (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
his research aims to analyze the influence of Good Corporate Governance (GCG) on financial distress in State-Owned Enterprises (SOEs) listed on the Indonesia Stock Exchange during the COVID-19 pandemic. GCG is measured through the variables of Independent Commissioners, Board of Directors, and Audit Committee. The data is analyzed using descriptive statistical methods and the Wilcoxon Signed Rank Test. The results of the research indicate that Independent Commissioners, Board of Directors, and Audit Committee have a significant effect on financial distress in SOEs during the research period. This suggests that the implementation of good GCG principles can help reduce the risk of financial distress in SOEs in Indonesia. or formula.